2018
DOI: 10.1021/acsenergylett.7b01196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cs on the Stability and Photovoltaic Performance of 2D/3D Perovskite-Based Solar Cells

Abstract: One of the attractive features of hybrid perovskite is the possibility to reduce its dimensionality, which enhances the perovskite's resistivity to moisture. In this work, we used 2D/3D perovskites to study different organic molecular spacers (aromatic ring vs cyclic ring); Cs was introduced as an additional small cation to methylammonium. It was found that Cs improves the photovoltaic performance; however, it reduces the cells' stability because two cations having a different ionic radius are mixed, which cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 27 publications
(36 reference statements)
1
55
0
Order By: Relevance
“…As a distinctive factor between 2DPs and 3DPs, the spacer cation is naturally one important parameter to optimize. For example, better thermal and moisture stability can be obtained simply by using a spacer cation with a longer carbon chain or with an aromatic ring . Long chains will also reduce conductivity and aggravate charge accumulation; hence, an optimum length needs to be found to balance stability and efficiency .…”
Section: Discussionmentioning
confidence: 99%
“…As a distinctive factor between 2DPs and 3DPs, the spacer cation is naturally one important parameter to optimize. For example, better thermal and moisture stability can be obtained simply by using a spacer cation with a longer carbon chain or with an aromatic ring . Long chains will also reduce conductivity and aggravate charge accumulation; hence, an optimum length needs to be found to balance stability and efficiency .…”
Section: Discussionmentioning
confidence: 99%
“…However, standard operational conditions for photovoltaics require materials and devices to be stable at this temperature. Therefore, the replacement of the organic parts by inorganic components (Cs + ) is expected to dramatically increase the long‐term stability . It has been widely reported that even a small amount of cesium can greatly enhance the thermal stability of organic–inorganic hybrid perovskites .…”
Section: Introductionmentioning
confidence: 99%
“…While contactless time-resolved microwave conductivity measurements contradictorily suggest a much lower carrier lifetime of the same material ( 13 ). Recent investigations in the quasi-2D perovskite suggested a scaling law for excitons ( 14 , 15 ), and solar cells based on 2D/3D mixed halide perovskites have shown the success for simultaneously improved power conversion efficiency and stability ( 12 , 16 – 18 ), which, however, raises the fundamental questions about the depleted and accumulated charge carriers at the 2D/3D hetero-interfaces, similar to the issues in GaAs/Al x Ga 1− x As superlattice ( 19 ), since the 3D perovskite has an energetically lower conduction band and may act like an electron acceptor in the 2D/3D mixed phase. Overall, these contradictory results from different reports and the questions about the nontrivial boundary relevant properties cannot be completely explained by solely considering the bulk physics without taking into account the edge effect.…”
Section: Introductionmentioning
confidence: 99%